Shelf-Life Prediction of Shredded Duck “Cahyo” by Accelerated Shelf-Life Testing (ASLT) technique Based on The Arrhenius Model - Febrianti, Nadya Dwi Putri; Yulistiani, Ratna; Wicaksono, Luqman Agung; Purnama, Afridho Laksono Indra (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Shredded Duck